Ruined Landscapes, Sweaty Bodies - Tsing, Anna; Zhou, Feifei (Kronos, 2025)
This photo essay examines the ecological, social, and existential transformations wrought by sand mining in Sorong, Papua, where the relentless demand for concrete has reshaped both landscapes and human lives. Sand mining, driven by the forces of industrialisation and colonial legacy, fuels the growth of cities built on ecological ruin. Through the intertwined stories of settler miners and indigenous Papuans, the essay reveals how mining reduces both land and labor to extractable commodities: hills into sand and men into muscle and sweat.